Overall effectiveness of pneumococcal conjugate vaccines: An economic analysis of PHiD-CV and PCV-13 in the immunization of infants in Italy - Paolo Castiglia; Lorenzo Pradelli; Stefano Castagna; Veronica Freguglia; Giorgio Palù; Susanna Esposito (Taylor & Francis Group, 2017)
Pneumococcal diseases are associated with a significant clinical and economic burden. The 7-valent pneumococcal conjugate vaccine (PCV-7) has been used for the immunization of newborns against invasive pneumococcal diseases (IPD) in Italy while now, the pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) and the 13-valent pneumococcal conjugate vaccine (PCV-13) are available. The aim of this analysis was to compare the estimated health benefits, cost and cost-effectiveness of immunization strategies vs. non-vaccination in Italy using the concept of overall vaccine effectiveness. A published Markov model was adapted using local data wherever available to compare the impact of neonatal pneumococcal vaccination on epidemiological and economic burden of invasive and non-invasive pneumococcal diseases, within a cohort of newborns from the Italian National Health Service (NHS) perspective. A 18-year and a 5-year time horizon were considered for the base-case and scenario analysis, respectively. PHiD-CV and PCV-13 are associated with the most important reduction of the clinical burden, with a potential marginal advantage of PHiD-CV over PCV-13. Compared with no vaccination, PHiD-CV is found on the higher limit of the usually indicated willingness to pay range (30,000 - 50,000€/quality-adjusted life year [QALY] gained), while the incremental cost-effectiveness ratio (ICER) for PCV-13 is slightly above. Compared with PCV-13, PHiD-CV would provide better health outcomes and reduce costs even at parity price, solely due to its differential effect on the incidence of NTHi acute otitis media (AOM). The analysis on a shorter time horizon confirms the direction of the base-case.